Graph Based Approach For Multi Document Summarization (International Journal of Engineering and Computer Science, 2015)
Summarization is the process of decreasing large source document to shorten version of summary which will be easy to read. Document summarization is an emerging technique which is used for understanding the main purpose of any kind of documents. Summarization can be either single or multi document summarization. If summary is to be generated for single document then it is called as single document summarization. If summary is to be created for multiple relevant documents then it is called as multi document summarization. An Graph based approach for Multi Document Summarization is a graph based multi document summarization technique in which, set of documents is preprocessed, undirected graph will be constructed to calculate similarity between sentences, the word class is attached to each sentence, sentences are ranked according to word class and similarity of sentences and top ranked sentences are included in the summary.